Comparative Investigation into the Complexation and Extraction Properties of Tridentate and Tetradentate Phosphine Oxide‐Functionalized 1, 10‐Phenanthroline Ligands toward Lanthanides and Actinides. Issue 41 (8th June 2021) - Xu, Lei; Hao, Yuxun; Yang, Xiao; Wang, Zhipeng; Xu, Chao; Borisova, Nataliya E.; Sun, Mingze; Zhang, Xingwang; Lei, Lecheng; Xiao, Chengliang
Abstract: Two new phosphine oxide‐functionalized 1, 10‐phenanthroline ligands, tetradentate 2, 9‐bis(butylphenylphosphine oxide)‐1, 10‐phenanthroline (BuPh‐BPPhen, L 1 ) and tridentate 2‐(butylphenylphosphine oxide)‐1, 10‐phenanthroline (BuPh‐MPPhen, L 2 ), were synthesized and studied comparatively for their coordination with trivalent actinides and lanthanides. The complexation mechanisms of these two ligands toward trivalent f‐block elements were thoroughly elucidated by NMR spectroscopy, UV/vis spectrophotometry, fluorescence spectrometry, single‐crystal X‐ray diffraction, solvent extraction, and theoretical calculation methods. NMR titration results demonstrated that 1 : 1 and 1 : 2 (metal to ligand) lanthanides complexes formed for L 1, whereas 1 : 1, 1 : 2 and 1 : 3 lanthanide complexes formed for L 2 in methanol. The formation of these species was validated by fluorescence spectrometry, and the corresponding stability constants for the complexes of Nd III with L 1 and L 2 were determined by using UV/vis spectrophotometry. Structures of the 10‐coordinated 1 : 1‐type complexes of EuL 1 (NO3 )3 and [EuL 2 (NO3 )3 (H2 O)] Et2 O in the solid state were characterized by X‐ray crystallography. In solvent‐extraction experiments, L 1 exhibited extremely strong extraction ability for both Am III and Eu III, whereas L 2 showed nearly no extraction toward Am III or Eu III due to its high hydrophilicity. Finally, the structures and bonding natures of the complex species formed between Am III /Eu III and L 1 /L 2 were analyzed in DFT calculations. Abstract : The same, but different : Two phosphine oxide‐functionalized 1, 10‐phenanthroline ligands, the tetradentate 2, 9‐bis(butylphenylphosphine oxide)‐1, 10‐phenanthroline (L 1 ) and tridentate 2‐(butylphenylphosphine oxide)‐1, 10‐phenanthroline (L 2 ), have been synthesized and studied comparatively for coordination and extraction with trivalent actinides and lanthanides. Although quite different extraction properties toward Am III and Eu III were found between L 1 and L 2 due to their different hydrophobicity in nitrate media, they showed comparable affinity to trivalent f‐block elements, as revealed by UV/vis titration, single‐crystal X‐ray diffraction and DFT calculation.